2022
DOI: 10.1002/ppul.26034
|View full text |Cite
|
Sign up to set email alerts
|

Breath sound analyses of infants with respiratory syncytial virus acute bronchiolitis

Abstract: Introduction:The reliability of a breath sound analysis using an objective method in infants has been reported.Objective: Breath sounds of infants with respiratory syncytial virus (RSV) acute bronchiolitis were analyzed via a breath sound spectrogram to evaluate their characteristics and examine their relationship with the severity. Subjects and Methods:We evaluated the inspiratory and expiratory breath sound parameters of 33 infants diagnosed with RSV acute bronchiolitis. The sound powers of inspiration and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…In this study, we were able to obtain data from age‐matched control infants and were able to demonstrate the specificity of acute bronchiolitis. RSV acute bronchiolitis is probably characterized by the presence of specific narrowing of the peripheral airways due to thick sputum and severe epithelial damage 13 . One of the points of this study is whether or not lung sound analysis can help distinguish between bronchiolitis and non‐bronchiolitis in infants, and we were indeed able to demonstrate the potential utility of this method.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…In this study, we were able to obtain data from age‐matched control infants and were able to demonstrate the specificity of acute bronchiolitis. RSV acute bronchiolitis is probably characterized by the presence of specific narrowing of the peripheral airways due to thick sputum and severe epithelial damage 13 . One of the points of this study is whether or not lung sound analysis can help distinguish between bronchiolitis and non‐bronchiolitis in infants, and we were indeed able to demonstrate the potential utility of this method.…”
Section: Discussionmentioning
confidence: 71%
“…Wheezes is thought to be a sound originating from the bronchi that occurs when air of respiration passes through the narrowing part, and rhonchi is thought to be a sound of vibration mainly by viscous sputum in the airways due to the air flow 27 . In our previous study, we reported that the rhonchi of acute bronchiolitis pointed out by the attending physician was recognized as a non‐uniform, belt‐like pattern in the lung sound spectrogram (Figure 1a), such as bands that look like a series of particles in the low range 13 . Low‐tone intermittent sounds that occur continuously at very short intervals possibly heard as rhonchi.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations